A potential relationship between soccer shoes and pes cavus: a pilot study - Stephan Becker; Lukas Maurer; Carlo Dindorf; Jonas Dully; Michael Fröhlich; Oliver Ludwig (BMC Sports Science, Medicine and Rehabilitation)
Abstract Background Preventive team testing showed an above-average number of pes cavus among soccer players. This raised the question of whether wearing relatively small soccer shoes - as it is often the case for soccer players - shoes might be responsible and cause a kind of foot compression and a muscular-induced pes cavus. Methods This cross-sectional study included 198 male youth and adult soccer players (age: 18.6±5.8 years, height: 176.3±14.8 cm, body mass: 69.9±11.5 kg). The delta between shoe and foot length was compared with arch index (AI) and normalised truncated navicular height (NTNH) and especially for those whose shoes were too small. Results The data confirms that among soccer players, 34% had a pes cavus, only 15% were free of pes planus or pes cavus and 27% wore shoes that were too small. Contrary to the authors hypothesis, the NTNH revealed a general relationship with the delta between foot length and shoe length. Players with shoes that were too small had a significantly higher arch (AI = 0.24) than players with adequate shoe size (AI = 0.25), but on average, the arch was still in the range of a normal foot. No correlation was found between the magnitude of the delta and the AI value for the subgroup of players whose shoes that were too small. Conclusions The data confirm the increased prevalence of pes cavus among soccer players, but could not confirm the authors’ hypothesis that this may be caused by wearing shoes that are too small.